Understanding aspect ratio effects in Laser Powder Bed Fusion of polyamide 12 by means of infrared thermal imaging - Greiner, Sandra; Drummer, Dietmar (Procedia CIRP, 2022)
Laser powder bed fusion of polymers (LPBF-P) is a very promising additive manufacturing technology, as it allows for the generation of complexly shaped parts with high mechanical properties. However, enhancing the reproducibility of part properties is still one of the main challenges. Therefore, the basic material beam interactions and the resulting temperature fields have to be fully understood. Within this contribution, the influences of part geometry and exposure parameters on temperature fields and layer formation are investigated. Infrared thermal measurements were conducted during laser exposure under variation of the aspect ratio of the part cross-section. An extensive part characterization was carried out in order to correlate the temperature values to part properties. For thermal history, it is clearly visible that the scan vector length is a more decisive parameter than the number of parallel scan vectors, but with respect to layer formation, the number of parallel hatches has to be considered as well. According to these results, optimum specifications for process parameters can be derived.
Created from Fastlane, Scopus look-up
Keywords: Exposure; Laser Sintering; Polyamide 12; Powder bed fusion of polymer; Thermal Imaging